Math, asked by xiawong, 1 year ago

plzzzz answer this question ​

Attachments:

Answers

Answered by yash3374
0

Answer:

Hey mates

Hear is your answer

yaar tumhara writing samaj me nhi aa rha h sorry

please post again this question.

Answered by ambarkumar1
1

3/2 x – 2/3y = 7/6

LCM = 6

Multiplying each term with LCM

3x × 3 – 2y × 2 = 7

9x – 4y = 7 – ( 1 ) × 2

2x – 3y = 10 – ( 2 ) × 9

Multiplying equation (1) by 2 and (2) by 9

18x – 8y = 14

18x – 27y = 90

_(–)_(+)____(–)___

19y = – 76

y = – 76 / 19

y = – 4

Put y = – 4 in equation (2)

2x – 3(–4) = 10

2x + 12 = 10

2x = 10 – 12

2x = – 2

x = – 1

Ans : ( 1 , 4 )

Hope the solution is clear to you!!

Similar questions